2005
DOI: 10.1002/jsfa.2331
|View full text |Cite
|
Sign up to set email alerts
|

Changes in quality characteristics during cold storage of shucked mussels (Mytilus galloprovincialis) and selected chemical decomposition indicators

Abstract: The following chemical changes were observed during the cold storage of mussels for 6 days at 4 • C. Total volatile basic nitrogen (TVB-N, mg N per 100 g) and trimethylamine values (TMA-N, mg N per 100 g) were increased from 22.55 and 5.96 mg per 100 g at day 0 to 12.38 and 0.42 mg per 100 g, respectively, at the end of the storage period. The indole value and putrescine concentration were increased from 15.36 µg kg −1 and 24.7mg kg −1 to 34.46 µg kg −1 and 63.86 mg kg −1 , respectively, on the fourth day of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 34 publications
3
23
1
2
Order By: Relevance
“…Similar results on the initial pH of mussels were reported as 5.96 by Erkan 24 . Mussels pretreated with lactic acid had lower pH than those pretreated with chitosan.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar results on the initial pH of mussels were reported as 5.96 by Erkan 24 . Mussels pretreated with lactic acid had lower pH than those pretreated with chitosan.…”
Section: Discussionsupporting
confidence: 88%
“…Erkan 24 reported that the TVB-N value of fresh mussel was initially 12.38 mg N 100 g -1 , reaching 22.55 mg N 100 g -1 after the sixth day. Goulas et al 28 found that the TVB-N value was initially 11.48 mg N 100 g -1 in mussel samples and it was 36.72 mg N 100 g -1 after 15 days of storage for the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bivalve TVN values were similar in samples of the two aliquots. The bivalve levels found were lower than those reported by Erkan (2005) for shelled mussels stored at 4°C. In clams TVN values were not statistically different.…”
Section: Resultscontrasting
confidence: 82%
“…These results suggest that histamine is the best indicator of decomposition for mussels stored at elevated temperature. In contrast, Erkan (29) reported a signifi cant increase in putrescine levels in blue mussel decomposed at 4 °C. Mackie et al (30) confi rmed very low histamine and considerable putrescine, cadaverine, and agmatine production in the muscle of another decomposing molluscan shellfi sh, Atlantic scallop (Pecten maximus) at 0 °C.…”
Section: Biogenic Amines In Mediterranean Blue Musselmentioning
confidence: 84%